1996
DOI: 10.1152/ajpgi.1996.271.3.g448
|View full text |Cite
|
Sign up to set email alerts
|

Role of cholecystokinin as a regulator of solid and liquid gastric emptying in humans

Abstract: The role of endogenous cholecystokinin (CCK) in the regulation of gastric emptying remains controversial. We therefore studied the effect of the CCK-A receptor antagonist loxiglumide on gastric emptying of a high-caloric solid-liquid meal in humans. Gastric emptying was assessed in eight volunteers using intravenous loxiglumide or placebo in a randomized double-blind order. Subjects were studied by a dual-headed gamma camera after ingestion of a pancake (570 kcal) labeled with 99mTc-sulfur colloid and 500 ml 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
26
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 0 publications
3
26
0
Order By: Relevance
“…Similarly, 5-HT 3 receptor participation in the control of gastric emptying has also been demonstrated to be mediated along capsaicin-sensitive extrinsic afferent nerve fibers (4). In view of the fact that CCK and 5-HT activate distinct separate populations of vagal afferent fibers (23), the present findings suggest that CCK-induced suppression of sham feeding is mediated along vagal afferent fibers not directly originating from 5-HT 3 receptors.…”
Section: Discussionsupporting
confidence: 59%
See 4 more Smart Citations
“…Similarly, 5-HT 3 receptor participation in the control of gastric emptying has also been demonstrated to be mediated along capsaicin-sensitive extrinsic afferent nerve fibers (4). In view of the fact that CCK and 5-HT activate distinct separate populations of vagal afferent fibers (23), the present findings suggest that CCK-induced suppression of sham feeding is mediated along vagal afferent fibers not directly originating from 5-HT 3 receptors.…”
Section: Discussionsupporting
confidence: 59%
“…One such response is the mediation of nutrient-induced inhibition of gastric emptying (49). Similar to 5-HT, one mechanism by which CCK suppresses food intake is through its ability to inhibit gastric emptying (3,12,19,36,40,43,55).Previous studies have shown an interaction between the serotonergic and cholecystokinergic systems in the control of food intake (7,8,47). Although original exploration of this interaction focused on central serotonergic activity, recent reports (11), including those from our own laboratory (22), have shown that systemic administration of a selective 5-HT 3 receptor antagonist attenuates CCK-induced satiation.…”
mentioning
confidence: 99%
See 3 more Smart Citations